Adjuvant radiotherapy improves progression-free survival in intracranial atypical meningioma - Saman Moritz Hemmati; Pirus Ghadjar; Arne Grün; Harun Badakhshi; Sebastian Zschaeck; Carolin Senger; Güliz Acker; Martin Misch; Volker Budach; David Kaul (Radiation Oncology, 2019)
Abstract Background Meningiomas are the most common primary tumors of the central nervous system. In patients with WHO grade I meningiomas no adjuvant therapy is recommended after resection. In case of anaplastic meningiomas (WHO grade III), adjuvant fractionated radiotherapy is generally recommended, regardless of the extent of surgical resection. For atypical meningiomas (WHO grade II) optimal postoperative management has not been clearly defined yet. Methods We conducted a retrospective analysis of patients treated for intracranial atypical meningioma at Charité Universitätsmedizin Berlin from March 1999 to October 2018. Considering the individual circumstances (risk of recurrence, anatomical location, etc.), patients were either advised to follow a wait-and-see approach or to undergo adjuvant radiotherapy. Primary endpoint was progression-free survival (PFS). Results This analysis included 99 patients with atypical meningioma (WHO grade II). Nineteen patients received adjuvant RT after primary tumor resection (intervention group). The remaining 80 patients did not receive any further adjuvant therapy after surgical resection (control group). Median follow-up was 37 months. Median PFS after primary resection was significantly longer in the intervention group than in the control group (64 m vs. 37 m, p = 0.009, HR = 0.204, 95% CI = 0.062–0.668). The influence of adjuvant RT was confirmed in multivariable analysis (p = 0.041, HR = 0.192, 95% CI = 0.039–0.932). Conclusions Our study adds to the evidence that RT can improve PFS in patients with atypical meningioma.